Analisa Kemampuan Komunikasi Interpersonal Najwa Shihab Melalui Akun Instagram @Najwashihab - Suci Shinta Lestari; Kukut Kurniawati (Fakultas Dakwah dan Komunikasi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Najwa Shihab’s interpersonal communication skills can be used as a role model for other women to increase their capacity to communicate so that they can get out of injustices such as marginalization, subordination, double burden, stereotypes and violence. With better communication, the occurrence of gender bias can be expected. Women are no longer considered as someone who does not have the skills to lead or speak in public as public speakers. There are several women who got out of this stereotype. One of them is Najwa Shihab. This study uses a qualitative method using the theory of The Five Canons Of Rhetoric, with content analysis and documentation data collection techniques. The subject of this research is Najwa Shihab’s Instagram @najwashihab. From the results of the study, it was concluded that Najwa Shihab always prioritized thorough preparation as a communicator or public speaker. From the results of the analysis, I concluded that Najwa Shihab explored the topic before the broadcast started. He collected detailed and detailed data before researching the speaker. Najwa Shihab always composes and organizes his messages logically and there is no repetition of words. Najwa Shihab also speaks according to facts and does not exaggerate to create a dramatic effect. The information always contains a message or message in every show that is delivered simply. His style is firm and often interacts using body talk to his speakers.